ANALISIS PERGANTIAN KANTOR AKUNTAN PUBLIK DAN KETEPATAN WAKTU DALAM PELAPORAN TERHADAP REAKSI PASAR (Studi empiris pada perusahaan manufaktur yang terdaftar di BEI) - Sony Cokro Handoko; Sudarno Sudarno (Diponegoro Journal of Accounting, 2015)
This research aims to analyse the effect of auditor switching and timelines on theinvestor behavior which is indicated by market reaction of the 50 companies listed on the Indonesian Stock Exchange on the date of reporting at the Financial Service Authority (OJK) inthe period 2009-2012.The study used a measuring tool cumulative abnormal returns around the date of auditor switching listed on the Stock Exchange and the date of the financial statement reporting to the Financial Services Authority. This study also adds control variables are firm size, tenure, and ROA.The result of the analysis show that there is a markets’ reaction, which is indicated by negative cumulative abnormal stock return around the date of auditor- switching and a significant positive to the timelines. Based on the result, I conclude that there is an information content of auditor-switching, and investor percieved that as a bad news. The result also show us that the companies which submit timely the report to the public in accordance with the rules, is the company that the performances better than the companies that are not on time.